Governance implications of the UN higher education sustainability initiative. Issue 4 (18th April 2018) - Moon, Christopher J.; Walmsley, Andreas; Apostolopoulos, Nikolaos
Abstract : Purpose: This paper aims to review the progress of a sample of ( n = 307) signatories in the Higher Education Sustainability Initiative which commits higher education institutions (HEIs) to make smart commitments to achieve one or more of the UN sustainable development goals (SDGs). Design/methodology/approach: A preliminary survey of n = 307 HEIs via online questionnaire and database search was conducted. Findings: Findings reveal a difference between HEI governance, that is "instrumental", and governance, that is "holistic", in relation to sustainability. Research limitations/implications: Implications identified for achieving SDGs in general and for academic–business partnerships, in particular. Practical implications: Practical implications for enterprise (developing a tool to measure sustainability mindset) and for enterprise education (sharing of best practices from other HEIs). Social implications: Improved understanding of the sustainability mindset will inform decisions about approaches to governing and operationalising sustainability in organisations. Originality/value: The survey is not original but the emphasis on sustainability mindset (compassion, empathy and connectedness to SDGs) is.